(untitled) (Education in the 21st Century, 2023)
Left-handedness, being a feature of personality, and sometimes being on the same content level as education and training, has completely different requirements. It includes unintended, spontaneous influences, thanks to which a person adapts to society and becomes a full and full member of society.Note that the formation of left-handed characteristics does not always begin with the appropriate moment of existence and the creation of relationships with other people. That is why the left-handed child should be considered not only as a biological organism, but also as a social being who can transform himself to adapt to the social environment.The adaptation process of left-handed children leads to radical changes in the organization of teaching in public schools, transforming teaching methods, technologies, in particular, teacher-left-handed student relations. In order to study the process of manifestation of left-handedness in a public school, it is necessary to refer to the diagnostic methods of left-handedness, which is transferred from the biological and social sphere to the sphere of pedagogy. Therefore, it is important to study it in the unity of social and pedagogical processes.